2013
DOI: 10.5863/1551-6776-18.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron to Treat Pruritus Due to Cholestatic Jaundice

Abstract: Intractable itching is a symptom of cholestatic liver disease of various causes that is bothersome and difficult to manage. Although treatment of the primary cause of cholestasis is paramount in resolving the issue, given the debilitating consequences of pruritus, symptomatic treatment is frequently necessary. Although many medications including cholestyramine, rifampin, opioid antagonists (i.e., naloxone, naltrexone), phenobarbital, and antihistamines have been used to treat cholestatic-induced pruritus, none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Antihistamines are often clinically prescribed to cure or alleviate pruritus. However, owing to the existence of histamine-independent itch pathways, antihistamines are mostly ineffective for various chronic itch conditions such as cholestasis 2,26,27 . Till date, various histamine-independent pruritogens have been reported, such as chloroquine 28 , β-alanine 29 , TSLP 30 , IL-31 31 , SLIGRL-NH 2 32 , and BAM8-22 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Antihistamines are often clinically prescribed to cure or alleviate pruritus. However, owing to the existence of histamine-independent itch pathways, antihistamines are mostly ineffective for various chronic itch conditions such as cholestasis 2,26,27 . Till date, various histamine-independent pruritogens have been reported, such as chloroquine 28 , β-alanine 29 , TSLP 30 , IL-31 31 , SLIGRL-NH 2 32 , and BAM8-22 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical observation showed that administration of 5-HT 3 receptor antagonist ondansetron3435363738 or selective serotonin reuptake inhibitor (SSRI) sertraline3940 were able to alleviate cholestatic pruritus, providing important clues to support key role of 5-HT system in cholestatic pruritus. Unfortunately, little is known of the modulatory effects of peripheral and central 5-HT system, especially 5-HT receptor subtypes, on cholestatic pruritus and antinociception so far7374.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of multiple 5-HT receptors subtypes may explain their complex influence on the processing of pain or itch signal2528303233. Interestingly, several clinical trials found that administration of 5-HT 3 receptor antagonist ondansetron3435363738 or selective serotonin reuptake inhibitor (SSRI) sertraline3940 were able to alleviate cholestatic pruritus, providing important clinical evidence to support critical role of 5-HT system in cholestatic pruritus. Although the importance of 5-HT system is emphasized in the modulation of pain and itch252641, the possible roles of peripheral and spinal 5-HT receptors in itch and antinociception induced by cholestasis are still unclear.…”
mentioning
confidence: 99%
“…Intravenous 5-HT3-receptor antagonist ondansetron has been shown to have antipruritic effect in cholestatic patients with conflicting results [ 57 ]. It may also have an effect on opioid pathways.…”
Section: Hepatogenic Pruritusmentioning
confidence: 99%